Seroprevalence of Equine Leptospirosis in the State of Goiás, Brazil - Tatiana Nunes de Azevedo Romanowski; Ricardo Augusto Dias; Marcos Bryan Heinemann; Stephani Félix Carvalho; Tamires Ataides Silva; Andressa da Silva Martins; Geovanna Domingues da Cunha Caetano; Álvaro Ferreira Júnior; Jandra Pacheco dos Santos; Ana Carolina Borsanelli (Veterinary Sciences, 2023)
Leptospirosis, caused by Leptospira, is a zoonotic disease that, in horses, is linked to abortions, uveitis, and sporadic occurrences of liver and kidney disease, often resulting in significant economic losses for farmers. Research on the prevalence of leptospirosis in horses in the central-west region of Brazil has been relatively scarce. Thus, the present study aimed to determine the prevalence of leptospirosis in equine herds in the state of Goiás (Central Brazil). Blood samples were collected from 894 equids at 294 randomly selected farms divided into three different strata according to their herd characteristics. The microscopic agglutination test for the detection of anti-Leptospira agglutinins was carried out and the results showed that among the 294 sampled farms, 213 (72.9%; CI 95% 71.7–78.9) had one or more animals positive for leptospirosis, and of the 894 horses sampled, 513 (61.6%; CI 95% 54.3–69.0) were seropositive for leptospirosis. Djasiman, Icterohaemorrhagiae, and Australis were the most prevalent serogroups. The results showed a high prevalence of seropositive animals and a widespread distribution of positive farms in the state of Goiás. Thus, environmental sanitation measures and health education to prevent and control equine leptospirosis in the state are required.